Pancreatic Neoplasm in 2011: An Update - Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
Pancreatic cancer still is a significant, unresolved therapeutic challenge with nearly similar incidence and mortality rates. It is the most lethal type of digestive cancer with a 5-year survival rate of 5%. Adjuvant chemotherapy remains to be gemcitabine alone or combined with infusional 5-fluorouracil with radiation therapy. Nevertheless, only a few patients survive for at least 5 years after R0 resection and adjuvant therapy. Most patients need palliative treatment. Once pancreatic cancer becomes metastatic, it is uniformly fatal with an overall survival of typically 6 months from diagnosis. Chemotherapy is an important component of palliative care but must be administered as a part of a multidisciplinary approach, including palliation of pain, managing weight loss, and deterioration in functional status. Gemcitabine has been the standard in both locally advanced and metastatic disease. The addition of the tyrosine kinase inhibitor erlotinib prolongs median survival for only 2 weeks. While gemcitabine-based regimens are currently accepted as the standard first-line treatment of patients with locally advanced or metastatic pancreatic adenocarcinoma, there is no consensus regarding treatment in the second-line setting. It will not be untrue to say that there are no real medical breakthroughs with regards to improving the prognosis of pancreatic cancer as of 2011. On the other hand, we have made some progress in patients with advanced pancreatic neuroendocrine tumors. These patients have a 5-year survival that can range from 97% in benign insulinomas to as low as 30% in non-functional metastatic pancreatic neuroendocrine tumors. Treatment options may include surgery, transarterial chemoembolization of liver metastases, and cytotoxic therapy such as streptozotocin, 5-fluorouracil or doxorubicin. Somatostatin analogues, like octreotide, have been proven to prolong progression-free survival in patients with metastatic neuroendocrine tumors of midgut origin. In 2011, two targeted agents, a tyrosine kinase inhibitor sunitinib and mTOR inhibitor everolimus have been approved by FDA for pancreatic neuroendocrine tumors. With these approvals, U.S. physicians can now offer their patients with progressive pancreatic neuroendocrine tumors. Patients with any stage of pancreatic cancer should be considered candidates for clinical trials. Image: Mode of action of everolimus.